Determination of the antioxidant and enzyme-inhibiting activities and evaluation of selected terpenes' ADMET properties: in vitro and in silico approaches - Touhtouh, Jihane; Laghmari, Mustapha; Benali, Taoufiq; Aanniz, Tarik; Lemhadri, Ahmed; Akhazzane, Mohamed; Habbadi, Khaoula; Bouyahya, Abdelhakim; Zengin, Gokhan; Hammani, Khalil (Biochemical systematics and ecology, 2023)
The in vitro antioxidant capacity of eugenol, eucalyptol, linalool, and carvacrol was performed using six test systems: phosphomolybdenum, DPPH (2,2′-diphenyl-1-picrylhydrazyl radical), ABTS (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonate), CUPRAC (cupric ion reducing antioxidant capacity), FRAP (Ferric reducing ability of plasma), and metal chelating effect. Their inhibitory activities on cholinesterases, α-amylase, α-glucosidase, and tyrosinase were assessed as well. Molecular docking helped to explain the obtained outcomes while in silico ADMET (absorption, distribution, metabolism, excretion, and toxicity) prediction served for assessing the physicochemical and pharmacokinetic profiles. Our findings showed that the examined terpenes have promising antioxidative activity with eugenol and carvacrol displaying the highest efficiency. Linalool presented the highest anti-AChE and anti-tyrosinase activities (7.931 ± 0.034 mg GALAE/g and 58.707 ± 5.120 mg KAE/g, respectively). Eucalyptol exhibited the strongest anti-BChE activity (2.704 ± 0.025 mg GALAE/g), while carvacrol exhibited the highest rates for α-glucosidase and α-amylase inhibition (1.414 ± 0.042 and 1.023 ± 0.054 mM ACAE/g, respectively). Molecular docking revealed that all compounds interacted in varied ways with the five enzymes’ active sites. Excellent binding profiles and greatest inhibitory activity to AChE (−7.4 kcal/mol), α-glucosidase (−6.5 kcal/mol), and α-amylase (−6.5 kcal/mol) was attributed to carvacrol. As regards to tyrosinase, eugenol (−6.2 kcal/mol) was the potent one whereas carvacrol and eugenol (−6.5 kcal/mol for both) strongly interacted with BChE. Furthermore, in silico ADMET-related physicochemical and pharmacokinetic properties revealed good profiles. To sum up, here we demonstrate the powerful antioxidant potency and enzymatic inhibitory effects of the four terpenes which may enable the discovery of lead compounds that are extremely potent antioxidants and enzyme inhibitors. •Eugenol and carvacrol displayed potent antioxidant effect.•Linalool potently inhibited activity of acetylcholinesterase (AChE) and tyrosinase.•Eucalyptol exhibited the strongest inhibitory activity against butyrylcholinesterase (BChE).•Carvacrol exhibited the highest rates for α-glucosidase and α-amylase inhibition.